Diagnosis and treatment challenges of parathyroid carcinoma in a 27-year-old woman with multiple lung metastases. (13th March 2017) - Rozhinskaya, Liudmila; Pigarova, Ekaterina; Sabanova, Ekaterina; Mamedova, Elizaveta; Voronkova, Iya; Krupinova, Julia; Dzeranova, Larisa; Tiulpakov, Anatoly; Gorbunova, Vera; Orel, Nadezhda; Zalian, Artur; Melnichenko, Galina; et al.
Summary: Parathyroid carcinoma is an extremely rare disorder with little treatment options. It could be misdiagnosed in medical centers with little experience in management of such cases. Our clinical case shows that the initial misdiagnosis of a parathyroid carcinoma in a young woman has led to the development of multiple lung metastases, thus making its treatment hardly possible. Initiation of treatment with sorafenib – a multi-kinase inhibitor approved for treatment of different types of cancer but not parathyroid carcinoma – has led to a significant decrease in the size of lung metastases and has prevented the progression of hyperparathyroidism, which is usually severe in cases of parathyroid carcinoma. The detection of a germline CDC73 mutation in this patient has raised additional concerns about the necessity of periodic screening for early detection of renal, jaw and uterine lesions. Learning points: Diagnosis of parathyroid carcinoma may be challenging due to the absence of reliable diagnostic criteria. Thus, thorough histological examination is needed using immunohistochemical staining of resected tissue in suspicious cases. CDC73 genetic testing should be considered in patients with parathyroid carcinoma. Sorafenib may be a promising treatment of patients with parathyroid carcinoma with distant metastases.